Improving Productivity in Integrated Fish-Vegetable Farming Systems with Recycled Fish Pond Sediments - Chau Thi Da; Phan Anh Tu; John Livsey; Van Tai Tang; Håkan Berg; Stefano Manzoni (Agronomy, 2020)
The increasing intensification of aquaculture systems requires the development of strategies to reduce their environmental impacts such as pollution caused by the discharge of nutrient rich sediments into local water bodies. Recycling of fish pond sediments (FPS) as fertilizer has been proposed as a possible solution that may also reduce the reliance on synthetic fertilizers. With a case study in the Mekong Delta, Vietnam, we determined suitable mixtures of striped catfish (Pangasianodon hypophthalmus) pond sediment (PPS) and locally sourced organic amendments of rice straw (RS), or common water hyacinth (WH) to fertilize cucumber plants (Cucumis sativus L.) in an integrated cucumber–giant gourami fish (Osphronemus goramy) farming system. Highest nutrient concentrations were found when mixing 30% PPS with 70% RS or WH. When used in combination with chemical fertilizer, it was found that a 25% to 75% reduction in chemical fertilizer application could be achieved, while also increasing cucumber yields, with the highest yields found when RS was used in organic amendments. In combination with the additional income from fish production, integrated farming systems such as that demonstrated in this study, may increase both farm income and production diversity.